High precision, high time-cadence measurements of the MgII index of solar activity by the GOES-R Extreme Ultraviolet Irradiance Sensor 2: EUVS-C initial flight performance - McClintock William E.; Snow Martin; Eden Thomas D.; Eparvier Francis G.; Machol Janet L.; Woodraska Donald L. (Journal of Space Weather and Space Climate)
EUVS-C is one component of the Extreme Ultraviolet Irradiance Sensor (EUVS) instrument. EUVS, together with the X-ray sensor (XRS), comprise the Extreme Ultraviolet and X-ray Irradiances Sensors (EXIS) investigation (Machol JL et al. 2020. The GOES-R series: a new generation of geostationary environmental satellites, pp. 233–242. https://doi.org/10.1016/B978-0-12-814327-8.00019-6) aboard the GOES-R satellite series, which includes GOES-16, -17, -18, and -19. From their vantage points in geostationary orbit, the EUVS-C instruments measure the solar MgII Index, also referred to as the MgII core-to-wing-ratio, which is a proxy for chromosphere activity and correlates with solar extreme ultraviolet (EUV) emission. MgII produces two bright chromosphere emission lines appearing in the sun’s spectrum at 279.55 nm and 280.71 nm (MgII k and h) that appear in the cores of their respective photospheric absorption lines. Measuring the ratio of emission from the core (chromospheric) to that from the wings (photospheric) provides an index that is relatively insensitive to changes in instrument performance. In 2005, Snow & McClintock used 0.1 nm resolution data to show that the intrinsic solar variability in the index (as opposed to instrument noise) is on the order of 0.2% on time scales of 5–10 min. EUVS-C is designed to exceed these performance requirements. A companion paper describes the instrument design and its pre-flight calibration. This paper describes the operational implementation of the algorithm that produces the Index, flight calibrations, and the initial instrument flight performance. Each EUVS-C currently operating (GOES-16, -18, and -19) is providing high time-cadence (3 s), high precision (1 part in 104) Index determinations. Spectral shifts arising from spacecraft orbital motion introduce a systematic 0.1% diurnal variation in absolute index values. Additionally, wavelength-dependent radiometric responsivity degradation leads to a systematic increase in the reported index on a timescale of years at an average rate of 0.2% per year. These systematic effects can be mitigated with additional post-data processing.